Step
*
2
1
of Lemma
fun_exp_compose
1. T : Type
2. n : ℤ
3. 0 < n
4. ∀[h,f:T ⟶ T].  ((f^n - 1 o h) = primrec(n - 1;h;λi,g. (f o g)) ∈ (T ⟶ T))
5. h : T ⟶ T
6. f : T ⟶ T
⊢ (primrec(1 + (n - 1);λx.x;λi,g. (f o g)) o h) = primrec(1 + (n - 1);h;λi,g. (f o g)) ∈ (T ⟶ T)
BY
{ ((InstLemma `primrec_add` [⌜T ⟶ T⌝]⋅ THENA Auto) THEN RWO "-1" 0 THEN Auto THEN Reduce 0) }
1
1. T : Type
2. n : ℤ
3. 0 < n
4. ∀[h,f:T ⟶ T].  ((f^n - 1 o h) = primrec(n - 1;h;λi,g. (f o g)) ∈ (T ⟶ T))
5. h : T ⟶ T
6. f : T ⟶ T
7. ∀[n,m:ℕ]. ∀[b:T ⟶ T]. ∀[c:ℕn + m ⟶ (T ⟶ T) ⟶ T ⟶ T].
     (primrec(n + m;b;c) ~ primrec(n;primrec(m;b;c);λi,t. (c (i + m) t)))
⊢ ((f o primrec(n - 1;λx.x;λi,g. (f o g))) o h) = (f o primrec(n - 1;h;λi,g. (f o g))) ∈ (T ⟶ T)
Latex:
Latex:
1.  T  :  Type
2.  n  :  \mBbbZ{}
3.  0  <  n
4.  \mforall{}[h,f:T  {}\mrightarrow{}  T].    ((f\^{}n  -  1  o  h)  =  primrec(n  -  1;h;\mlambda{}i,g.  (f  o  g)))
5.  h  :  T  {}\mrightarrow{}  T
6.  f  :  T  {}\mrightarrow{}  T
\mvdash{}  (primrec(1  +  (n  -  1);\mlambda{}x.x;\mlambda{}i,g.  (f  o  g))  o  h)  =  primrec(1  +  (n  -  1);h;\mlambda{}i,g.  (f  o  g))
By
Latex:
((InstLemma  `primrec\_add`  [\mkleeneopen{}T  {}\mrightarrow{}  T\mkleeneclose{}]\mcdot{}  THENA  Auto)  THEN  RWO  "-1"  0  THEN  Auto  THEN  Reduce  0)
Home
Index